Study on fire performance of T-shaped concrete-filled steel tubular stubs under axial compression. (1st August 2022) - Yang, Weiqi; Yang, Yuanlong; Liu, Faqi; Wei, Xuan; Chen, Yohchia Frank
Abstract: Six T-shaped concrete-filled steel tubular (TCFST) stubs under axial compression loading were designed and tested under the ISO-834 standard fire curve. The temperature field distribution, axial deformation development, fire resistance and failure mode of TCFST columns under fire were investigated. The fire test results showed that the fire resistance decreases with the increase of axial compression ratio; the fire resistance of the tension bar stiffener column is 18% higher than that of the multi-cell column (the fire resistance values are 89 min and 73 min respectively); the fire resistance of specimens increases linearly with the thickness of the fire protection layer. Then the fire behavior of TCFST columns is analyzed by the ABAQUS software. The simulated temperature distribution and fire resistance are in good agreement with the test results. Meanwhile, the fire resistance is slightly higher than that of the square CFST column in the standard 'Technical Code for Concrete Filled Steel Tubular Structures (GB50936-2014)'. Furthermore, a parametric analysis results show that slenderness ratio, column limb thickness, eccentricity ratio and fire protection layer thickness have influences on the fire resistance. It is found that the first level fire-resistance rating of TCFST columns can be achieved by adopting a reasonable thickness of the fire protection layer. At last, simplified formulas of the fire resistance and the fire protection layer are proposed, and the simplified formula can reduce up to 50% of the thickness of the fire protection layer compared to current fire design requirements for CFST columns. Highlights: The T-shaped concrete-filled steel tubular (TCFST) columns were tested under the ISO-834 standard for fire first time. The temperature distribution and the axial deformation of TCFST column were researched by the ABAQUS based on fire test. The simplified formulas for fire resistance and fire protection layer are proposed for fire design of TCFST column.